Study of Transportation of Gtl Products From Alaskan North Slope (ANS) to Markets - Chukwu, Godwin A. (Petroleum Development Laboratory (United States), 2002)
The Alaskan North Slope is one of the largest hydrocarbon reserves in the US where Gas-to-Liquids (GTL) technology can be successfully implemented. The proven and recoverable reserves of conventional natural gas in the developed and undeveloped fields in the Alaskan North Slope (ANS) are estimated to be 38 trillion standard cubic feet (TCF) and estimates of additional undiscovered gas reserves in the Arctic field range from 64 TCF to 142 TCF. Transportation of the natural gas from the remote ANS is the key issue in effective utilization of this valuable and abundance resource. The throughput of oil through the Trans Alaska Pipeline System (TAPS) has been on decline and is expected to continue to decline in future. It is projected that by the year 2015, ANS crude oil production will decline to such a level that there will be a critical need for pumping additional liquid from GTL process to provide an adequate volume for economic operation of TAPS. The pumping of GTL products through TAPS will significantly increase its economic life. Transporting GTL products from the North Slope of Alaska down to the Marine terminal at Valdez is no doubt the great challenge facing the Gas to Liquids options of utilizing the abundant natural gas resource of the North Slope. The primary purpose of this study was to evaluate and assess the economic feasibility of transporting GTL products through the TAPS. Material testing program for GTL and GTL/Crude oil blends was designed and implemented for measurement of physical properties of GTL products. The measurement and evaluation of the properties of these materials were necessary so as to access the feasibility of transporting such materials through TAPS under cold arctic conditions. Results of the tests indicated a trend of increasing yield strength with increasing wax content. GTL samples exhibited high gel strengths at temperatures as high as 20 F, which makes it difficult for cold restart following winter shutdowns. Simplified analytical models were developed to study the flow of GTL and GTL/crude oil blends through TAPS in both commingled and batch flow models. The economics of GTL transportations by either commingled or batching mode were evaluated. The choice of mode of transportation of GTL products through TAPS would depend on the expected purity of the product and a trade-off between loss in product value due to contamination and cost of keeping the product pure at the discharge terminal.